2017
DOI: 10.4038/cjs.v46i1.7413
|View full text |Cite
|
Sign up to set email alerts
|

Toxin producing freshwater cyanobacteria of Sri Lanka

Abstract: Abstract:Cyanobacteria are photosynthetic, prokaryotic microorganisms commonly found among the phytoplankton of stagnant waters. Some of them produce toxins and these have been implicated to contribute to environmental health problems including kidney disease of uncertain etiology. This paper is a review of published literature on freshwater cyanobacteria of Sri Lanka with special emphasis on toxigenic genera. It is evident that the freshwater cyanobacterial populations of Sri Lanka have undergone significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…One ecosystem approach is to replace chemical-based nitrogen and phosphate fertilizers with organic fertilizers in crop production, while improving soil health. This would, for example, help reduce water pollution and prevent the overgrowth of toxin-producing cyanobacteria [156]. Switching from chemical-based phosphate fertilizers to organic fertilizers would also help reduce arsenic exposure [167].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One ecosystem approach is to replace chemical-based nitrogen and phosphate fertilizers with organic fertilizers in crop production, while improving soil health. This would, for example, help reduce water pollution and prevent the overgrowth of toxin-producing cyanobacteria [156]. Switching from chemical-based phosphate fertilizers to organic fertilizers would also help reduce arsenic exposure [167].…”
Section: Discussionmentioning
confidence: 99%
“…Toxigenic cyanobacteria present a growing problem in Sri Lanka’s waterways, particularly in the North Central province where CKDu is endemic [156]. It is clear that their overgrowth is related to human activities, particularly in agricultural areas, where agricultural runoff of phosphate and nitrate fertilizers are supporting their growth.…”
Section: Synergy Between Glyphosate and Other Toxic Elementsmentioning
confidence: 99%
“…In particular, the toxin-producing cyanobacteria genera, including Microcystis and Cylindrospermopsis , as well as Leptospira interrogans can lead to kidney disease 14 , 18 , 24 , 25 and have, therefore, been put forward as potential causes of CKDu 21 , 26 , 27 . Significant increases of cyanobacteria in freshwater resources in Sri Lanka have occurred over the past century as a result of eutrophication and rising temperatures 21 , 28 , demonstrating that altered water chemistry is likely to promote the presence of pathogenic bacteria in this region.…”
Section: Introductionmentioning
confidence: 99%
“…4 25 20 24 23 3 44 40 39 34 42 41 26 28 10 16 27 12 38 11 35 43 17 33 31 18 21 19 15 13 22 9 45 32 36 5 29 7 14 30 8 6 8 6 14 29 7 5 33 27 32 28 26 12 45 44 42 34 40 38 30 31 18 13 35 16 43 36 15 19 17 11 41 37 9 10 21 22 23 24 25 20 39 4 3 Perera et al, (2012b). Cyanobacterial species are known to occur under different limnological conditions as they can tolerate wider ranges of temperature, light and nutrient conditions which are important for their survival (Kulasooriya, 2017). These tolerance levels of different species determine the dominance and community structure of phytoplankton at different periods and seasons (Fogg, 1975).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Unfortunately, a quantitative assessment was not done to get a clear idea on the role of macrophytes in absorbing nutrients. When considering the presence of dominant toxic algae in macrophyte dominant reservoirs, it was interesting to see that species such as C. rasciborski and M. aeruginosa are not available showing importance of macrophytes in balancing an ecosystem (Kulasooriya 2017). Weerakoon et al (1998) also reported that high density and diversity of aquatic macrophytes in Basawakkulama reservoir compared to Tisawewa may provide a favourable ecological niche to zooplanktons which will regulate the Cylindrospermopsis abundance.…”
Section: Cluster Analysismentioning
confidence: 99%